Structural and functional changes of the heart in patients with diabetic nephropathy undergoing hemodialysis - O. B. Susla; Z. I. Litovkina; O. V. Bushtynska (Ukrainian Journal of Nephrology and Dialysis, 2019)
Systematic analysis of cardiac remodeling peculiarities in patients with V D stage of chronic kidney disease (CKD VD)  caused by diabetes mellitus is important both in the stratification of cardiovascular risk and in the choice of adequate treatment strategies.The purpose of the study was to determine the character of structural and functional reconstruction of myocardium in patients with diabetic nephropathy (DN) on maintenance hemodialysis (HD) by identifying left ventricular hypertrophy (LVH), its geometric types, assessment of the severity of heart dysfunction, pulmonary hypertension (PH), as well as determination of frequency of cardiac valve calcification (CVC), development of defects of mitral (MV) and aortic (AV) valves.Materials and methods. The study included 136 patients on chronic HD (men, 78, age, (53,9±1,0) years, duration of HD, (47,6±4,2) months). Depending on the presence/absence of type 2 diabetes mellitus (DM) with kidney damage, they were divided into two groups: the first one – without DN (n=88); the second one – with DN (n=48). All patients were followed up by standard echocardiography (EchoCG) examination by standard procedure.Results. LVH was diagnosed in 84.6% of patients with CKD VD stage, significantly more often (93.8 vs. 78.4%, p=0.020) in patients with DN, with the incidence of eccentric LVH in the second group being higher (47.9 vs. 28.4%, p=0.023) than in the first one. Prevalence of pseudonormal and restrictive types of LV diastolic dysfunction (62.5 vs. 28.4%, p<0.001), LV systolic dysfunction (27.1 vs. 9.1%, p=0.006) and PH (64.6 vs 35.2%, p=0.001) were significant in HD patients with DN. CVC was detected in 66.6% of patients with type 2 DM with renal injury with a predominance of calcification of both valves (35.4%) over isolated calcification of MV (MVC) (20.8%) and AV (AVC) (10.4 %). Combined valve calcification in the HD patients of the second group was observed 2.6 times more often (p=0.003) than in the first one. Patients with DN, unlike those without diabetes, were associated with a higher prevalence of stenoses of MV (16.7 vs. 3.4%, p=0.007) and AV (39.6 vs. 15.9%, p=0.004), and insufficiency of MV (66.7 vs. 44.3%, p=0.013) and AV (35.4 vs. 14.8%, p=0.006). The most significant EchoCG parameters that distinguished groups of HD patients with the presence of DN were: left atrial diameter (p<0.001), end-diastolic LV dimension (p<0.001), thickness of interventricular septum (p=0.001), LV myocardial mass index (p=0.001), ratio of transmitral flows in early and late diastole (p=0.009), time of deceleration of early diastolic transmitral blood flow (p<0.001), LV ejection fraction (p=0.009), diameter of the right ventricle (RV) (p=0.003), diameter (p=0.007) and mean pulmonary artery pressure (p<0.001).Conclusions. In patients with CKD VD stage with DN the maladaptive cardiac remodeling with predominance of unfavorable types (eccentric (to a greater extent) and concentric) LV hypertrophy, RV dilatation, PH, expressive of LV diastolic and systolic dysfunction, large-scale combined MVC and AVC occurs, which, in turn, leads to the formation of valve defects, can contribute to the progression of diastolic myocardial stiffness and heart failure.